Experimental and Theoretical Studies on the Effect of Die Temperature on the Quality of the Products in High-Pressure Die-Casting Process - Mohammad Sadeghi; Jafar Mahmoudi (Advances in Materials Science and Engineering)
Die temperature in high-pressure die casting of A380 alloy is optimized by experimental observation and numerical simulation. Ladder frame (one part of the new motor EF7) with a very complicated geometry was chosen as an experimental sample. Die temperature and melt temperature were examined to produce a sound part. Die temperatures at the initial step and the final filling positions were measured and the difference between these values was calculated. ProCAST software was used to simulate the fluid flow and solidification step of the part, and the results were verified by experimental measurements. It is shown that the proper die temperature for this alloy is above 200°C.